Development of Decision Support System for Corrosion under Insulation (CUI) for Austenitic Stainless Steels and Carbon Steels - Mohd Kamal Aizat Bin Ahmad, Mohd Kamal (Universiti Teknologi Petronas, 2008)
CUI is hazardous because insulation can become wet or contaminated, accelerating corrosion process. Moreover, CUI is particularly serious because it is difficult to predict and to detect. This report is basically brief about the research done and fundamental concepts of the chosen topic, which is; Development of decision-support system for Corrosion under Insulation (CUI) for austenitic stainless steels and carbon steels. The aim of the research project is to develop a decision support system (DSS) to determine the probability of equipment failure due to CUI. The research study consists of two phase, first phase is developing decision support system (DSS) using Microsoft Visual Basic 6.0. Second phase is develop knowledge base database for Corrosion under Insulation (CUI) and combining it into the decision support system (DSS) to create a stand-alone software that can determine the probability of equipment failure due to CUI. The objectives of the stand-alone software are to help and assist people to make decision more precise and accurate. The development of the Decision Support for Corrosion under Insulation (CUI) susceptibility is completed as scheduled.